Faktor Yang Berhubungan Dengan Kejadian Kekurangan Energi Kronik (KEK) Pada Ibu Hamil - Ningsih, Nurul Syuhfal; Wahyuni, Indah Sri (Bunda Edu-Midwifery Journal (BEMJ), 2022)
Pregnant women are prone to malnutrition because they have increased nutritional needs for the mother and fetus. Therefore, pregnant women often experience Chronic Energy Deficiency (KEK). Based on the results of a preliminary study conducted at the Independent Practice of Midwife Ritta Nurhayati in 2021, 34 out of 50 pregnant women experienced chronic energy deficiency obtained from the results of the LILA measurement. The results showed that there was a relationship between education, occupation, income, nutritional intake, ANC examination with the incidence of chronic energy deficiency in pregnant women.